2015
DOI: 10.1007/s13197-015-2060-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of alginate/carboxyl methyl cellulose composite coating incorporated with clove essential oil on the quality of silver carp fillet and Escherichia coli O157:H7 inhibition during refrigerated storage

Abstract: The effects of alginate/carboxyl methylcellulose composite coating incorporated with clove essential oil on quality of silver carp fillet chilled storage (4 + 1°C) were examined over a period of 16 days. The control samples (c), alginate/carboxyl methylcellulose coating (C-A), alginate/ carboxyl methylcellulose composite coating incorporated with clove essential oil (with different concentration 1 and 1.5 %) (C-A + CEO1 % and C-A + CEO 15 % respectively) were analyzed by bacteriological (total viable counts (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 30 publications
4
24
0
Order By: Relevance
“…The results of this study coincided with the results of researchers like Jalali et al. (), which indicated that coating treatment containing clove oil 1.5% was able to inhibit the growth of the inoculated Ashirosilicum bacterium in the phytofag fillet and to adhere to the acceptable level.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The results of this study coincided with the results of researchers like Jalali et al. (), which indicated that coating treatment containing clove oil 1.5% was able to inhibit the growth of the inoculated Ashirosilicum bacterium in the phytofag fillet and to adhere to the acceptable level.…”
Section: Resultssupporting
confidence: 91%
“…The results of this study in the total bacterium is consistent with results obtained by Ariaii, Tavakolipour, Rezaei, Elhamirad, and Bahram () on the coating of fish fillet with carboxymethylcellulose enriched with Pimpinella Affinis essential oil and results of Jalali, Ariiai, and Fattahi (), which investigates the effect of combined alginate‐carboxymethyl cellulose coating Clove oil to the amount of TVC filigree fillet.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Control samples remained fresh for about 6 days regarding the afore‐mentioned standard level; but, AL, AL–RE 0.1%, and AL–RE 0.2% could preserve the trout freshness for 9, 15, and up to 15 days of refrigerated storage, respectively. Decreasing water loss and oxygen permeability along with slowing growth bacteria, the sodium alginate coating could extend the shelf life of tout fillet (Jalali et al, ; Song et al, ). According to the results, as an antioxidant maintaining fish freshness in all storage periods, RE can be associated with the fast decrease in the bacterial population and bacterial ability of oxidative deamination in non‐protein nitrogen compounds.…”
Section: Resultsmentioning
confidence: 99%
“…Main components of clove essential oil are eugenol, β-caryophyllene, α-humulene, and eugenyl acetate. Studies on clove essential oil incorporated into an alginate-based edible film assured the safety and quality of fresh-cut 'Fuji' apples [88] and silver carp fillet [89]. The observed increase in shelf life extension of fresh-cut food products packed in alginate-based active nanocomposite was due to the antimicrobial activity of clove essential oils against common foodborne pathogens [90].…”
Section: Seaweed and Essential Oil Based Composite Materialsmentioning
confidence: 99%